Prenatal differential diagnosis of placental mesenchymal dysplasia and molar disease with coexistent live twin fetuses - Do Hwa Im; Young Nam Kim; Hwa Jin Cho; Min Jeong Kwon; Hye Kyoung Yoon; Da Hyun Kim; Byoung Jin Min; Jung Mi Byun; Dae Hoon Jeong (Clinical and Experimental Obstetrics & Gynecology)
Background: Numerous hypoechoic cysts in the placenta on prenatal ultrasonography with a live fetus may indicate twin pregnancy with a complete hydatidiform mole with a coexistent fetus, partial mole, confined placental mosaicism, or placental mesenchymal dysplasia (PMD). Ultrasonographic appearances of these are similar; however, the differential diagnosis should be made because maternal and fetal prognoses differ. Cases: We present two cases of twin pregnancies with numerous placental cystic lesions. The first case was a partial hydatidiform mole in monochorionic diamniotic twins with a diploid karyotype that underwent a spontaneous abortion at 20 gestational weeks. The second case was PMD in dichorionic diamniotic twins; live twin neonates were delivered at 34 gestational weeks. Emergency cesarean section delivery was performed due to severe preeclampsia and fetal growth restriction in twin A at 34 weeks of gestation. Conclusions: Numerous hypoechoic cysts in the placenta on prenatal ultrasonography with a normal live fetus warrants chromosomal analysis and serial ultrasonographic examination to differentiate between PMD and molar pregnancy with a coexisting normal fetus to avoid unnecessary termination.